Morphological study of the vertebral column and thoracic cage of the Rüppell's fox (Vulpes rueppellii) in the Benghazi area - Youssef , Abdulgader K.; Ahmed, Ahmed W.; Darnawi, Neema A. (Libyan Journal of Science &Technology, 2025)
The vertebral column and thoracic cage of a Rüppell's fox from the Benghazi area were morphologically investigated and described in this study. The fox’s vertebral formula was C7, T13, L7, S3, Ca22. In the middle of the pedicle, the fourth vertebra of the normal cervical vertebrae has a paddle-shaped process. The paired accessory processes of the thoracic vertebrae are found posteriorly beside the neural arch of the vertebrae. The dorsal side of the seventh vertebra of the caudal vertebrae has a narrow groove. There were a total of thirteen pairs of ribs. The first nine ribs were sternal, while the final three were asternal. The last rib was floating, and the sternum was made up of nine sternebrae arranged in cylindrical shape.